2020
DOI: 10.1002/alr.22635
|View full text |Cite
|
Sign up to set email alerts
|

An internally validated diagnostic tool for acute invasive fungal sinusitis

Abstract: BackgroundAcute invasive fungal sinusitis (AIFS) is a potentially life‐threatening diagnosis in immunocompromised patients. Identifying patients who could benefit from evaluation and intervention can be challenging for referring providers and otolaryngologists alike. We aimed to develop and validate an accessible diagnostic tool to estimate the probability of AIFS.MethodsRetrospective chart review from 1999 to 2017 identified all patients evaluated for possible AIFS at a tertiary care center. AIFS was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This is discordant with Turner et al [ 14 ], who described external debridement for 37.2%, endoscopic debridement in 37% and combined open and endoscopic debridement for 24.1% and Malleshappa et al [ 16 ] who recorded partial/total maxillectomy (29.4%), orbital exenteration (7.8%) and craniotomy (2%), while Allensworth et al [ 18 ] found that ten patients underwent maxillectomy, six with orbital exenteration. In concordance with a study done by Yin et al [ 15 ], most patients were treated with a combination of intravenous antifungal medication and surgery. Two patients passed away before surgery.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is discordant with Turner et al [ 14 ], who described external debridement for 37.2%, endoscopic debridement in 37% and combined open and endoscopic debridement for 24.1% and Malleshappa et al [ 16 ] who recorded partial/total maxillectomy (29.4%), orbital exenteration (7.8%) and craniotomy (2%), while Allensworth et al [ 18 ] found that ten patients underwent maxillectomy, six with orbital exenteration. In concordance with a study done by Yin et al [ 15 ], most patients were treated with a combination of intravenous antifungal medication and surgery. Two patients passed away before surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Extension into the orbit results in proptosis, deterioration in vision or even visual loss (70.4%), facial skin infarction, and ulceration in 46.3%. In addition, Yin et al [ 15 ] described that unilateral facial swelling, pain, or erythema were the most common presentations, involvement of the orbit or pterygopalatine fossa on imaging, and mucosal necrosis is seen on endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities suggestive of AIFS have included mucosal edema, discoloration (e.g., pallor or darkened tissue), ulceration, and lack of sensation. In general, select nasal endoscopy findings for AIFS are considered highly specific, but have a wide range in reported sensitivity, ranging from 49% to 75% 7,19,38,58,63,85,86 …”
Section: Endoscopymentioning
confidence: 99%
“…Other studies have developed diagnostic tools and based treatment protocols on CT imaging; however, early CT findings may be nondescript and may overlap with other entities. 9,43,44 In contrast, MRI provides greater sensitivity given the critical need to establish the diagnosis and to initiate prompt therapy. 10,13 Based on the present findings, initial MRI can be used to anticipate outcomes and potentially to assist in establishing care goals with the patient and family.…”
Section: Discussionmentioning
confidence: 99%